History of science and history of the book: the role of images as records of the knowledge on nature and art in early modern times - Roxo Beltran, Maria Helena (Circumscribere International Journal for the History of Science, 2015)
The interest of historians of science in the relationship between the generalization of the records of the knowledge on nature and art in printed books and the origins of modern science has increased since the beginning of the present century. However, few studies addressed the role of images in the recording and transmission of knowledge. Therefore, in the present article I aim at contributing to that subject, by discussing some aspects of the transformation of the function of images and their relationship with the written text in manuscripts and printed books alike, while paying particular attention to the records of the knowledge on nature and art in early modern times.